Private money and money market integration: The role of payments infrastructure in 19th century Switzerland - Daniel Kaufmann; Rebecca Stuart (Queen's University Centre for Economic History (QUCEH), 2024)
Using newly collected discount rate data for six Swiss cities, we find no evidence of increasing integration during a 30-year period of lightly regulated free banking. We attribute this to two structural issues: banks had incentives to protect their local monopolies, and the inherent instability of free banking meant that there was always a risk (which varied across banks) of a bank run. We use a novel counterfactual to show that these risks increased discount rate dispersion, and argue that as a result, public regulation of payments infrastructure was necessary for money market integration.
Keywords: E43; E44; F33; F45; N13; N23; 330; Switzerland; discount rates; money market; financial integration; monetary union; 19th century